TANGGUNG JAWAB PELAKU USAHA PENGIKLAN JIKA TERJADI KERUGIAN YANG DIALAMI OLEH KONSUMEN - Dian Kemalasari, Luh Putu; Artadi, I Ketut (Kertha Semaya : Journal Ilmu Hukum, 2013)
This paper is entitled “RESPONSIBILITIES OF ADVERTISING BUSINESS PERFORMER WHEN LOSSES SUSTAINED BY CONSUMERS”. Consumers and Interpretation of business performer is explained in Act No. 8 of 1999 on Consumers Protection. The objective of this paper is to find out how the responsibility of the advertiser’s business in the event of losses suffered by consumers. The method used in this paper is normative juridical research methods. Because of the losses suffered by consumers, manufacturers should be responsible for both criminal and civil. And responsibilities under in Act No. 8 of 1999 described in article 19 of BFL.
Keywords: Responsibilities, Business Performer, Losses, Consumer